Risk factors for bullying victimisation in a representative sample of Aotearoa New Zealand adolescents : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Manawatū, New Zealand - Birchall, Michael Greg (Massey University, 2021)
School bullying, or peer victimisation, involves the infliction of harm upon a weaker student on repeated occasions either through physical, verbal, or relational means. Research has consistently indicated that the prevalence of school bullying in Aotearoa New Zealand exceeds those observed in other developed countries. Bullying has been associated with considerable decrements in physical and mental health in developing adolescents. Addressing this issue requires an understanding of the risk and protective factors for bullying victimisation. Although these factors have been studied extensively overseas, there is a paucity of research in the Aotearoa New Zealand context. The present study investigated the risk factors for victimisation by conducting secondary analysis on a publicly available dataset. A self-report questionnaire carried out during the 2018 Programme for International Student Assessment (PISA) provided a large and representative sample of 15-year-old students in New Zealand secondary schools (n = 4,137). A multiple regression analysis revealed that of the ten potential risk factors eight were significantly associated with direct or indirect forms of bullying (or both). The risk factors with the largest effect sizes for victimisation were lower parental support, lower school belonging, increased classroom disorder, and increased competitiveness in the school climate. Moreover, the present study also included an analysis of the relationship between these risk factors and the adoption of anti-bullying attitudes. Being female rather than male, having higher parental support, and a more co-operative school climate was associated with lower tolerance of bullying expressed in students' attitudes. The results of this study suggest that some overseas findings concerning bullying risk can be extended to the New Zealand context and are discussed with respect to promising areas of future research.
Keywords: 520505 Social psychology